Frequency Analysis of Articulated Robot - Muhsin, Kadbim Karim (Basrah Journal for Engineering Sciences, 2008)
This paper presents a comprehensive frequency analysis of articulated robot. The purpose of a frequency response analysis is to compute the behavior of a articulated robot subjected to time-varying excitation. The transient excitation is explicitly defined in the time domain. The force applied to the structure is known at cach instant in time. Forces can be in the form of applied forces or enforced motions. The important results obtained from the frequency analysis are typically displacements, velocities, accelerations, eigenvalues, eigenvectors, and mode shapes of the robot nodes. Depending upon the structure and the nature of the loading, two different methods are used for the frequency response analysis direct and modal. The direct method performs an analytical analysis on the complete coupled equations of motion. The modal method utilizes the mode shapes of the robot to reduce and uncouple the equations of motion (when modal method is used); the solution is then obtained through the summation of the individual modal responses.